2022
DOI: 10.3390/ijms23179886
|View full text |Cite
|
Sign up to set email alerts
|

Novel Targets for a Combination of Mechanical Unloading with Pharmacotherapy in Advanced Heart Failure

Abstract: LVAD therapy is an effective rescue in acute and especially chronic cardiac failure. In several scenarios, it provides a platform for regeneration and sustained myocardial recovery. While unloading seems to be a key element, pharmacotherapy may provide powerful tools to enhance effective cardiac regeneration. The synergy between LVAD support and medical agents may ensure satisfying outcomes on cardiomyocyte recovery followed by improved quality and quantity of patient life. This review summarizes the previous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 199 publications
0
1
0
Order By: Relevance
“…Previous clinical studies have shown that renin-angiotensin-aldosterone system blockade, including with ACE inhibitors, improves reported quality of life, heart failure class, and LV function for patients with LVADs. 28 Our data showing that ACE inhibitor use in this patient population is associated with restored proteostasis (ie, reduction of ubiquitinated protein levels) may provide mechanistic insight into the underlying biology. It is therefore important to note that the high prevalence of ACE inhibitors used on our patient cohort post-LVAD may be a contributing factor to the molecular features observed.…”
Section: Discussionmentioning
confidence: 81%
“…Previous clinical studies have shown that renin-angiotensin-aldosterone system blockade, including with ACE inhibitors, improves reported quality of life, heart failure class, and LV function for patients with LVADs. 28 Our data showing that ACE inhibitor use in this patient population is associated with restored proteostasis (ie, reduction of ubiquitinated protein levels) may provide mechanistic insight into the underlying biology. It is therefore important to note that the high prevalence of ACE inhibitors used on our patient cohort post-LVAD may be a contributing factor to the molecular features observed.…”
Section: Discussionmentioning
confidence: 81%